1969
DOI: 10.1902/jop.1969.40.10.563
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Investigation of the Periodontal Changes During Pregnancy

Abstract: CHANGES IN THE GINGIVAL TISSUES during pregnancy have been termed "pregnancy gingivitis." During this period, the gingiva may appear hyperemic and enlarged and bleeding may be frequent during brushing or on external manipulation. Histopathologic evidence suggests that the microscopic changes observed in the gingiva during pregnancy do not differ from the microscopic changes observed in gingivitis in nonpregnant females. It is suggested that an accentuated inflammatory response to local irritants during pregnan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
78
1
3

Year Published

1976
1976
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(93 citation statements)
references
References 9 publications
11
78
1
3
Order By: Relevance
“…Our findings are in agreement with those reported by others authors like Cohen et al [4], Figuero et al [21] and Rashidi Maybodi et al [35], who observed a gradual increase in gingivitis from the first to the third trimester. The improvement during the postpartum was also described in studies by Raber-Durlacher [13] and Abraham-Inpijn et al [36], or the study of Gürsoy et al who concludes that changes in clinical parameters during pregnancy are reversible [37].…”
Section: Discussionsupporting
confidence: 94%
“…Our findings are in agreement with those reported by others authors like Cohen et al [4], Figuero et al [21] and Rashidi Maybodi et al [35], who observed a gradual increase in gingivitis from the first to the third trimester. The improvement during the postpartum was also described in studies by Raber-Durlacher [13] and Abraham-Inpijn et al [36], or the study of Gürsoy et al who concludes that changes in clinical parameters during pregnancy are reversible [37].…”
Section: Discussionsupporting
confidence: 94%
“…[61] Such findings suggest the existence of a relationship which is in agreement with those of many reports in the literature. [69,70,71,34] In agreement with the previous study found that the mean ± standard deviation of the decayed, missing and filled teeth was shown as 6.21 ± 1.4, 2.23 ± 0.9, 1.95 ± 0.9 respectively. [58] Lastly, the finding of the present study is in consistency with the result of Kornman and Loeshe who reported that one-quarter of the women of reproductive age had dental caries.…”
Section: Discussionsupporting
confidence: 90%
“…(2) Lower right first molar, mesial-lingual line angle; (3) Upper left central incisor, mesial-facial line angle; (4) Lower right central incisor, mesial-facial line angle.…”
Section: Methodsmentioning
confidence: 99%